Clinical and Immunological Profile of Mixed Connective Tissue Disease and a Comparison of Four Diagnostic Criteria. (29th January 2020) - John, Kevin John; Sadiq, Mohammad; George, Tina; Gunasekaran, Karthik; Francis, Nirmal; Rajadurai, Ebenezer; Sudarsanam, Thambu David
Abstract : Mixed connective tissue disease (MCTD) was initially described as a chronic immune-mediated disease with overlapping features of systemic lupus erythematosus, scleroderma, and polymyositis. We conducted a cross-sectional study to describe the clinical and immunological profile of patients with MCTD and to compare the four diagnostic criteria, namely, Sharp, Kasukawa, Alarcón-Segovia, and Khan criteria. A total of 291 patients who were admitted from June 2007 to June 2017 and fulfilled the inclusion criteria were included in the study. A clinical diagnosis of MCTD was made in 111 patients, of whom 103 (92.8%) were women. The mean age at presentation was 39.3 years (SD ± 11.6 ). The most common organ systems that were involved were musculoskeletal system (95.5%), skin and mucosa (78.4%), and the gastrointestinal and hepatobiliary systems (56%). The maximum sensitivity was for the Kasukawa criteria with a sensitivity of 77.5% (95% CI 68.4-84.6) and specificity of 92.2% (95% CI 87-95.5). The Kahn criteria and Alarcón-Segovia criteria had the maximum specificity; the Alarcón-Segovia criteria had a sensitivity of 69.4% (95% CI 59.8-77.6) and a specificity of 99.4% (95% CI 96.5-99.9), while the Kahn criteria had a sensitivity of 52.3% (95% CI 42.6-61.7) and a specificity of 99.4% (95% CI 96.5-99.9). The sensitivity and specificity of Sharp criteria were 57.7% (95% CI 47.9-66.87) and 90% (95% CI 84.4-93.8), respectively.